Experimental intra-abdominal hypertension influences airway pressure limits for lung protective mechanical ventilation (2013)
BACKGROUND: Intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) may complicate monitoring of pulmonary mechanics owing to their impact on the respiratory system. However, recommendations for mechanical ventilation of patients with IAH/ACS and the interpretation of thoracoabdominal interactions remain unclear. Our study aimed to characterize the influence of elevated intra-abdominal pressure (IAP) and positive end-expiratory pressure (PEEP) on airway plateau pressure (PPLAT) and bladder pressure (PBLAD). METHODS: Nine deeply anesthetized swineweremechanically ventilated via tracheostomy: volume-controlled mode at tidal volume (VT) of 10mL/kg, frequency of 15, inspiratory-expiratory ratio of 1:2, and PEEP of 1 and 10 cm H2O (PEEP1 and PEEP10, respectively). A tracheostomy tube was placed in the peritoneal cavity, and IAP levels of 5, 10, 15, 20, and 25 mm Hg were applied, using a continuous positive airway pressure system. At each IAP level, PBLAD and airway pressure measurements were performed during both PEEP1 and PEEP10. RESULTS: PBLAD increased as experimental IAP rose (y = 0.83x + 0.5; R2 = 0.98; p G 0.001 at PEEP1). Minimal underestimation of IAP by PBLAD was observed (j2.5 T 0.8 mm Hg at an IAP of 10-25 mm Hg). Applying PEEP10 did not significantly affect the correlation between experimental IAP and PBLAD. Approximately 50% of the PBLAD (in cm H2O) was reflected by changes in P PLAT, regardless of the PEEP level applied. Increasing IAP did not influence hemodynamics at any level of IAP generated. CONCLUSION: With minimal underestimation, PBLAD measurements closely correlated with experimentally regulated IAP, independent of the PEEP level applied. For each PEEP level applied, a constant proportion (approximately 50%) of measured PBLAD (in cm H2O) was reflected in PPLAT. A higher safety threshold for PPLAT should be considered in the setting of IAH/ACS as the clinician considers changes in VT. A strategy of reducing V T to cap PPLAT at widely recommended values may not be warranted in the setting of increased IAP. Copyright © 2013 Lippincott Williams and amp; Wilkins.